Love's awakening : a novel - Frantz, Laura (Frantz, Laura. Ballantyne legacy, 2013)
Ellie Ballantyne has left finishing school, and returns home to Pittsburgh. When she opens a day school for young ladies, she begins tutoring the incorrigible daughter of the enemy Turlock clan. The Turlocks are slaveholders and whiskey magnates, envious of the powerful Ballantynes and suspicious of their abolitionist leanings. As Ellie becomes increasingly tangled with the Turlocks, she finds herself falling in love with an impossible future-- and Jack Turlock, a young man striving to free himself from his family's violent legacy.